Peranan Hukum Positif Dalam Mengatur Cyberspace Untuk Menghadapi Tantangan Dan Peluang Di Era Digital - Ria Ermina Purba; Dewi Maharani; M. Akbar Adjiguna BMY; Raudatul Zahra Al Zahra (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The rapid development of information and communication technology has created a complex virtual environment known as cyberspace. In this digital era, cyberspace has become the main arena for various activities, from communication, business, to social interaction. However, this growth also poses serious challenges in managing these virtual spaces effectively. The role of law is very important in responding to this challenge. This study aims to explore the role of law in regulating cyberspace, as well as the associated challenges and opportunities. The role of law in this context includes establishing regulations, law enforcement, and protecting individual rights in the digital environment. The main challenges faced include the complex transnational nature of cybercrime, conflicting regulations between countries, as well as rapid legal adaptation to new technological developments. However, there are also emerging opportunities in regulating cyberspace. For example, the ability to apply a collaborative approach between states, the private sector and civil society in developing regulations that suit the unique characteristics of the digital environment. Additionally, technology can also be used as a tool to improve law enforcement and empower individuals to protect their privacy and security online. This study uses a descriptive analysis approach to evaluate relevant literature and case studies in order to understand the dynamics of the role of law in regulating cyberspace. By understanding these challenges and opportunities, we can develop a more holistic and adaptive framework for governing cyberspace, thereby ensuring the sustainability and security of the digital environment in this digital era.